Experimental study on the effect of fracture geometric characteristics on the permeability in deformable rough-walled fractures. (October 2017) - Chen, Yuedu; Liang, Weiguo; Lian, Haojie; Yang, Jianfeng; Nguyen, Vinh Phu
Abstract: The fracture geometric characteristics (FGC) have considerable influence on fluid flow in the fractured rock mass. The present work took experimental approaches to investigate the quantitative relationship between the FGC of a rough-walled fracture (RWF) and its hydraulic properties, particularly for the deformable fractures subjected to applied stresses. Taking into account the complexity of the FGC in realistic practice, the FGC studied in this work are comprised of three types: the size of apertures of interconnected void spaces, the contact areas of fracture surfaces, and the heterogeneous distribution of interconnected void spaces. In the proposed mathematical model, the above three FGC were represented by the corresponding parameters: the effective mechanical aperture, the contact ratio and the relative fractal dimension, respectively. In the experiment, six single fractured sandstone samples, divided into three groups by different grain sizes, were adopted for high-precision fluid flow tests under a variety of confining stresses. Firstly, to obtain the three-dimensional distribution of fracture morphology for each sample, we proposed a so-called point-cloud data matching method. This method is easy to operate and possesses high spatial resolution accuracy, meanwhile avoiding the destruction of the fracture surfaces. To explore effective percolation networks, the isolated void spaces between the two fracture surfaces, which are surrounded by contact regions and have no contribution to flow seepage, were identified and precluded from whole void spaces. Secondly, for each sample, the variation of the FGC representation parameters with confining stresses was quantitatively estimated in the laboratory. Lastly, an improved mathematical model was constructed to represent the relationship between fracture permeability and FGC representation parameters for RWF, which is also dependent on the confining stress. The theoretical values of hydraulic apertures predicted by our model were in good agreement with the experimental results. These results can account for the effect of the evolution of FGC on fracture permeability of deformable RWF.